The impact of compensation on job satisfaction: Work experience and education relationship - Anita Novialumi; Siti Dewi Winata (Annals of Human Resource Management Research, 2025)
Purpose: To explore the effect of compensation on job satisfaction by mediating the relationship between work experience and education among manufacturing workers in Bekasi City's food and beverage industry. Methodology: A quantitative approach with non-probability sampling. Data from 180 participants were analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS) through SmartPLS to assess variable relationships. Results: Work experience is positively associated with higher income and greater job satisfaction. Education likewise shows a significant positive relationship with salary and satisfaction. In addition, work-life balance enhances satisfaction. Furthermore, compensation operates as a mediating mechanism linking work experience and education to job satisfaction, indicating that gains from experience and education translate into satisfaction through pay. Conclusions: Compensation plays a pivotal mediating role in translating work experience and educational background into job satisfaction. Implementing competitive and equitable compensation strategies can effectively enhance job satisfaction among workers in the food and beverage manufacturing sector. Limitations: Non-probability sampling and focus on Bekasi City's food and beverage sector limit the generalizability of results. Contribution: Provides useful insights for HR managers and contributes to human resource management and organizational behavior literature on compensation and job satisfaction.